Women Exploitation in Jane Smiley's A Thousand Acres - Wirda Syifa'ul Ulya (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
A Thousand Acres by Jane Smiley is a fiction novel that explores the life of farmer’s family, where the novel discusses various problems related to the family, for example, the two main characters in the novel are portrayed as women in which they have accepted the exploitation of men in the scope of their family that dominates them greatly. This study aims to examine the representation of women exploitation experienced by female characters in the novel and also to identify the struggles of female characters to fight the exploitation described in the novel. The paper employs the theory of existential feminism by Simone de Beauvoir, in which she clearly explains the theory through how history and belief about the definition of women have been. The analysis reveals that the representation of women exploitation experienced by female characters is described in the novel by experiencing sexual abuse. Furthermore, in fighting the exploitation they have experienced, female characters try to free themselves by expressing anger and also escaping from depressing situations. This shows that women also have the right to freedom of life. Keywords: exploitation, struggles, feminism, existentialism.